Multistatic SAR Satellite Formations: Potentials and Challenges - Krieger, Gerhard; Moreira, Alberto (IEEE Geoscience and Remote Sensing Symposium, 2005)
This paper discusses the capabilities of multistatic SAR satellite configurations for different applications like high resolution DEM generation using multibaseline single-pass crosstrack interferometry, 3-D vegetation mapping and layover solution with spaceborne SAR tomography, high resolution wide swath SAR imaging with sparse satellite arrays, multibaseline velocity estimation of moving objects and scatterer fields, spatial and radiometric resolution enhancement in SAR images, and multistatic imaging for improved detection and classification. Furthermore, some major challenges like phase and time synchronisation, multistatic SAR processing, satellite orbit selection, and relative position sensing will be addressed. © 2005 IEEE.
DLR Import::2019-04-03